Nature of the Mau Forest Evictions in Kenya - Koech, Betty Chemutai (African Quarterly Social Science Review, 2024)
Protected areas such as national parks, conservation zones, and nature reserves are globally defined so by governments primarily to preserve the natural environment for the benefit of flora and fauna, that is, for the public good. Eviction of Forest communities is a result of this endeavour. The Ogiek community of the Mau Forest complex in Kenya have fallen victim to this.  The government declared the forest a protected area and hence evicting them contrary to Chapter Four of the Kenya Constitution that gives all Kenyans regardless of where they live, fundamental rights and freedoms. The evictions raise the question of what happens to the evictees’ human security. It is against this backdrop that this study set out to examine the nature of Mau Forest evictions in Kenya. The study used descriptive research design and had a sample of 472 respondents who included 384 household heads, 1 County Commissioner, 2 Deputy county commissioners, 7 chiefs, 32 village elders, 10 Police Officers, 1 UNEP Representative, 1 UN Habitat Representative, 10 Officers from Kenya Forest Service (KFS), 5 officers from Kenya Wildlife Service (KWS), 5 heads NGOs, Directore (NEMA), 10 Heads of CBOs. The study applied simple random and purposive sampling techniques. Interviews, questionnaires, FGDs and observation were used to collect primary data while secondary data was gathered from publications.  SPSS version 26 was used to analyse quantitative data and presented in tables, graphs, and charts. Narratives and verbatim quotations were used to present the qualitative data. The study found that the Mau forest evictions had negative effects on Ogiek human security, including deaths (86%), injuries (97%), destruction of homes (98%), farms (80%), livestock (52%), illness (95%), lack of sanitation (92%), gender-based violence (69%), disruption of schooling (100%), loss of culture (94%), separation from family (88%), loss of livelihoods (98%), and increased human-wildlife conflicts (78%), and 100% of respondents feared for their safety. The study recommends that, the government adopts a more humane and sustainable relocation policy and provide alternative ways of livelihood to the victims.